THE ROLE OF COLOR SYMBOLISM IN THE FORMATION OF NATIONAL IDENTITY: A LINGUOCULTURAL APPROACH - Djalilova Sarvaroy Mekhrojovna (Bright Mind Publishing, 2025)
This article examines the role of color symbolism in the formation of national identity through a linguocultural perspective. The semantics of colors in various cultures, particularly in Uzbek and Spanish, and their reflection in phraseology are analyzed. The study follows the IMRAD methodology, allowing for a structured analysis of historical and cultural aspects of color perception, as well as the influence of religion and traditions on national color perception.
Keywords: Colour symbolism, national identity, linguoculturology, color semantics, phraseology, cultural codes, ethnocultural specificity.